Human papilloma virus vaccines awareness among female medical and dental undergraduate students - Sharma, Vasudha; Bachhel, Rachna; Singh, Navyug Raj (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Human papilloma virus (HPV) infection is the major risk factor for cervical cancer. Pap smear is the commonest technique for early screening and diagnosis of cervical cancer. Methods: Cross sectional study was carried out at a medical and dental institution of Punjab, India, among 84 medical and dental female undergraduate students, falling in the age group of 18-25 years using a validated and guided questionnaire. Goal of the study was to raise the attention of the underrated and unaware agenda of prevention of cervical carcinoma by available vaccines. Results: 96.42%, 25%, population was aware of HPV vaccination in 3rd, 2nd, medical students respectively and 60.71% in 2nd year dental students. 8.33% of the whole population (n=84) was vaccinated against HPV. The main reasons of not taking the vaccination were that the students had not heard of such a vaccine followed by the cost of the vaccine. Conclusions: Medical and dental undergraduates are not adequately aware about the HPV vaccine and are not vaccinated in large number.